TEORI HIERARKI KEBUTUHAN ABRAHAM MASLOW SEBAGAI DASAR UNTUK MENINGKATKAN MOTIVASI BELAJAR MAHASISWA - Putri, Yollanda Cheriz Novita; Ibatiyani, Bunga (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2025)
College students are the nation's next generation, transitioning from adolescence to adulthood. During this period, they face various challenges that can affect their learning motivation. Abraham Maslow's Hierarchy of Needs Theory is believed to provide an understanding of the factors influencing learning motivation. The purpose of this study is to examine the role of Abraham Maslow's Hierarchy of Needs Theory in increasing student learning motivation and to identify the impact of fulfilling basic needs to self-actualization on learning enthusiasm. The method used was a literature review of national and international literature from 2021-2025 with the keywords